Assessment of heavy metals in Tehran's airborne particulate matters (PM4) and their associated health risk - Sohrab Mazloomi; Abbas Esmaeili Sari; Nader Bahramifar (علوم محیطی)
Introduction: Particulate matters are one of the most important air pollutants in Tehran and very dangerous for human health according to the epidemiological studies. The ambient particles contain heavy metals, some of which are toxic and carcinogenic components. Therefore, in this study, the content of heavy metals in airborne particulate matters (PM4) of Tehran was measured and the related health risk was assessed. Material and methods: Sampling of PM4 was conducted every six days using Chrono PM Sampler with a 10 L/min flow rate at two residential areas including Tehranpars in the east and Ekbatan in the west of Tehran. The concentration of PM4 was calculated with Gravimetric analysis. After the preparation of the samples using the extraction solution (HCl and HNO3), the concentration of heavy metals was measured by ICP-MS. The metal richness was assessed using the enrichment factor. For health risk assessment of heavy metals in PM4, excess cancer risk was calculated. Results and discussion: At both sampling stations, the highest concentrations in all PM4 samples were related to Al and Fe due to the high abundance of these elements in the earth's crust. The results of the enrichment factor indicated that Al, Fe, Ti and Mn in PM4 had low enrichment degree and the source of these metals might mainly be the earth's crust. Ni and Cr had a high enrichment degree. In addition, Zn, Pb, Cu, Sn, As, and Cd had a very high enrichment degree and were mainly anthropogenic. The concentration of PM4 was not significantly different between the two stations in the east and west, but the comparison of the mean concentration of metals in PM4 samples between the two stations showed that the concentrations of Mn, Cu, Sn, Ni, and As at the eastern station were significantly higher than the western station. The comparison of the enrichment factor between the two sampling stations also showed that the EF values of the studied elements at the eastern station were higher than those at the western station, which could indicate a higher contribution of anthropogenic sources in the east. Among the studied elements, the highest excess cancer risk was related to Cr(VI) due to its high toxicity. The total excess cancer risk based on the average concentrations of toxic metals in PM4 was 120.1×10-6 at the eastern station and 83.1×10-6 at the western station. Conclusion: Most of heavy metals in PM4in the east and west of Tehran had mainly anthropogenic sources and were generated by human activities, especially transportation. The average concentration of heavy metals in PM4 at the east of Tehran was higher than the west, and as a result, the excess cancer risk of toxic metals in PM4 was also higher in the east. The most dangerous carcinogenic element in particulate matters of Tehran was Cr(VI), which should be taken more under consideration and its anthropogenic emission sources must be controlled.